2006
DOI: 10.1097/01.bsd.0000211201.93125.1c
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Surgical Outcomes Between Macro Discectomy and Micro Discectomy for Lumbar Disc Herniation: A Prospective Randomized Study With Surgery Performed by the Same Spine Surgeon

Abstract: For herniotomy for lumbar disc herniation, both macro discectomy and microdiscectomy are appropriate, as long as surgeons have mastery of the procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
95
0
7

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(110 citation statements)
references
References 20 publications
8
95
0
7
Order By: Relevance
“…39 In addition, it was reported that minimally invasive surgery had the advantages of diminishing postoperative pain 40 and the rate of postoperative recurrence. 41 The postoperative complications are decreased after minimally invasive surgery. 42 Therefore, the hospitalization time could be reduced because of the good surgery result.…”
Section: Discussionmentioning
confidence: 99%
“…39 In addition, it was reported that minimally invasive surgery had the advantages of diminishing postoperative pain 40 and the rate of postoperative recurrence. 41 The postoperative complications are decreased after minimally invasive surgery. 42 Therefore, the hospitalization time could be reduced because of the good surgery result.…”
Section: Discussionmentioning
confidence: 99%
“…Despite a steep learning curve, bi-dimensional view and higher costs, several authors have reported on the reliability of this new technique in retrospective series [2,14], but a randomised clinical trial comparing MED with OD did not find significant differences in the main outcome indexes [20]. Meanwhile, MD and OD analysed in a prospective comparative study showed similar clinical outcomes [11], while MED and MD compared in another prospective comparative study behaved similarly [22].…”
Section: Introductionmentioning
confidence: 93%
“…Inclusion criteria to enter the study were a diagnosis of symptomatic, single level posterior lumbar disc herniation (LDH) made by spine specialists (orthopaedic and neurosurgeons) in patients aged 18-65 years with pain and/or neurological signs in concordant distribution lasting at least over 6 weeks of appropriate conservative treatment consisting of systemic drugs for pain relief and/or epidural steroid administration [3,6,11,18,20,21,23]. Exclusion criteria were less than 6 weeks of pain duration, cauda equina symptoms, foraminal or extra-foraminal herniations, cervical or lumbar spine stenosis of any aetiology, malignancy, previous spine surgery, spinal deformity including spondylolisthesis of any aetiology, concurrent infection and rheumatic disease [3,6,11,18,20,21,23].…”
Section: Admission Criteria and Recruitment Of Patientsmentioning
confidence: 99%
“…Katayama Y et al in randomized control study with macro and micro discectomy compared post operative analgesic requirement, functional outcome and VAS score found difference in operation time (40 minute vs 45 minutes), blood loss (29 gm vs 25 gm) hospital stay (8.3 days vs 8.5 days)but none of them were clinically relevant. 28 Shorter hospital stays, less blood loss and operation time are not related with better clinical outcome and not a predictor of reoccurrence sciatica or re-herniation.…”
mentioning
confidence: 99%